2003
DOI: 10.1002/adma.200305200
|View full text |Cite
|
Sign up to set email alerts
|

High Electron Mobility and Ambipolar Transport in Organic Thin‐Film Transistors Based on a π‐Stacking Quinoidal Terthiophene

Abstract: Thin‐film transistors (TFTs) based on a new n‐channel organic semiconductor (DCMT; see Figure) are reported. An electron mobility as high as 0.2 cm2/V s was observed, as well as ambipolar TFT behavior. Variable temperature measurements reveal that electron conduction is activated, with a small activation energy of 35 ± 10 meV. These results demonstrate that quinoidal oligothiophenes are a promising new class of organic semiconductors for TFTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
169
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(179 citation statements)
references
References 24 publications
8
169
0
1
Order By: Relevance
“…Ambipolar transport (i.e. encompassing both n-and p-types) was successfully achieved in a thin-film transistor using a quinoid oligothiophene derivative (Casado et al 2002(Casado et al , 2003Pappenfus et al 2002a,b;Chesterfield et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ambipolar transport (i.e. encompassing both n-and p-types) was successfully achieved in a thin-film transistor using a quinoid oligothiophene derivative (Casado et al 2002(Casado et al , 2003Pappenfus et al 2002a,b;Chesterfield et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these promising preliminary results there is still a drawback associated with most ambipolar OFETs reported to date, which is the relatively low carrier mobility. [7][8][9][10] For example, in the work by Meijer et al the maximum ambipolar carrier mobilities reported were in the order of 10 −5 cm 2 /V s (for both electrons and holes) for narrow band gap based polymeric OFETs, and 10 −5 cm 2 /V s (electrons) 10 −3 cm 2 /V s (holes) for OFETs based on polymer-small molecule interpenetrating networks. 7 Moreover, Dodabalapur et al have observed that the electron mobility in ambipolar OFETs employing an organic heterostructure of C 60 / ␣-6T is lower by a factor of 16 when compared with the electron mobility measured in pristine C 60 OFETs.…”
mentioning
confidence: 99%
“…1 Only very recently has ambipolar device operation been reported in field-effect transistors ͑FETs͒ based on a few different single-component 2 organic molecular semiconductors. [3][4][5][6] Some of these ambipolar devices have been used to realize inverter circuits that demonstrate the possibility of implementing complementary metal-oxide-semiconductor ͑CMOS͒ technology. 7 Since CMOS technology is the most efficient strategy toward the fabrication of integrated circuits with better noise margins ͑i.e.…”
mentioning
confidence: 99%